Studies of intestinal streptococcal urinary infections. First report of a work in progress - Colichón A., Héctor (1964)
An attempt to study streptococci or other bacteria in certain urinary or urogenital infections by applying the technique of gelation of plasma ( 1) is the main objective of the present work . This new technique provides some interesting data prematurely , as mobility, the trend microaerophilic , aerobic or anaerobic strain to be isolated . Dismissing the bacteria that ferment lactose with gas and using the method of serial dilutions, the gel can serve as a simple and easy technique for counting bacteria urine of patients that lead certain chronic conditions , particularly : pyelonephritis . Planting deep puncture in the gelled evidenced plasma fibrinolytic action (1, 2 ) many strains of enterococci , which may be of varying degrees and forms. In a first group of urinary patients studied , in which Enterococcus urine a small group of strains isolated from the faeces of patients suffering from chronic intestinal diseases was isolated , and , while fibrinolytic action already mentioned it was found , it was shown the frequency in these cases Enlerococos coagulase positive strains were isolated .